System-related influences on assigning patients to emergency care practitioners - Abd Hamid, Harris Shah; Waterson, Patrick (UniMap, 2011)
The deployment of advanced paramedics in ambulance services in the UK has been reviewed in the last few years. This study examined the role played by a computerised dispatch system (AMPDS – Advanced Medical Priority Dispatch System) which was reported to be not predictive in terms of selecting suitable patients to assign to emergency care practitioners (ECPs). The aim of this paper is to further examine the AMPDS data in order to understand influences on ECPs deployment and the resulting patient outcomes in an Ambulance Services NHS (National Health Service) Trust. AMPDS data for cases where ECPs were dispatched during a six-month period was extracted. The data was analysed using SPSS 12.0 to examine the number and types of cases across different time frames. In order to understand the factors related to ECP deployment and decisions to transport patients, semi-structured interviews were conducted with seventeen ECPs and three ambulance control room staff. The interviews were transcribed and analysed using emergent themes analysis with NVivo7. Results: There was an increase in the number of cases assigned to ECPs in the months covered by the data set. There are differences of the rate of patient transport among the Primary Care Trusts (PCT) within the Ambulance Services which are not due to fluctuations in workload across days of the week. The interviews help to explain the variations by identifying wider systemic influences. Themes derived from the interviews are patient’s social needs, geographical factor, technical factor, information factor, and connectivity to care pathways. Conclusions: The variations in the deployment of ECPs within the Ambulance Services can be partly attributed to wider systemic influences. Designing a paramedic role for pre-hospital care in the community should take into accounts the factors that influence their decisions regarding patient’s care pathway.